Transforming Student Satisfaction in the Digital Era: A Study of the Effects of Hybrid Learning and Digital Literacy in Islamic Religious Education - Husnul Mu'amalah (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the impact of hybrid learning and digital literacy on student satisfaction within Islamic Religious Education. As educational institutions increasingly adopt digital technologies, understanding their influence on student satisfaction is essential. A quantitative approach was employed using regression analysis to examine the relationship between hybrid learning, digital literacy, and their combined effects on student satisfaction. The study population consisted of 242 active students in the Islamic Education program at STIT Bustanul Ulum Anak Tuha, Lampung Tengah. A purposive sampling method was applied, selecting 65 students from the main campus based on specific criteria, including ownership of electronic devices and active enrollment. The findings demonstrate that flexibility and accessibility in hybrid learning, coupled with students' digital literacy, significantly enhance their overall satisfaction. Hybrid learning provides adaptive and personalized educational experiences, while digital literacy fosters comfort and engagement with online platforms. These factors collectively contribute to improved student satisfaction and learning outcomes. The results emphasize the need for universities to invest in robust digital infrastructure and provide targeted training programs to optimize hybrid learning environments. The implications of these findings extend beyond Islamic Religious Education, offering insights for other educational institutions aiming to enhance teaching strategies in the digital era. By prioritizing hybrid learning strategies and promoting digital literacy, universities can elevate student satisfaction and academic achievement, creating effective and adaptable learning environments for the future.